2020
DOI: 10.1039/d0tc04650g
|View full text |Cite
|
Sign up to set email alerts
|

Universal host materials for red, green and blue high-efficiency single-layer phosphorescent organic light-emitting diodes

Abstract: Simplifying the structure of Organic Light-Emitting Diodes (OLEDs) has been for the last twenty years the purpose of many studies. However, despite these efforts, only a few materials provide high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(105 citation statements)
references
References 86 publications
(95 reference statements)
3
102
0
Order By: Relevance
“…However, despite the logical implications for triplet energies and how these determine host/guest compatibility, it is not commonplace to report neat film phosphorescence of new OLED host materials. Instead, low temperature solution measurements currently dominate the literature in reports of this kind [69, 76–87] . A recent study by Forrest and Thompson [73] has demonstrated that such solution measurements do not give appropriate triplet energies for the design of OLEDs, while the results here show that phosphorescence in dilute polymer films is also not suitable in this regard.…”
Section: Resultsmentioning
confidence: 72%
“…However, despite the logical implications for triplet energies and how these determine host/guest compatibility, it is not commonplace to report neat film phosphorescence of new OLED host materials. Instead, low temperature solution measurements currently dominate the literature in reports of this kind [69, 76–87] . A recent study by Forrest and Thompson [73] has demonstrated that such solution measurements do not give appropriate triplet energies for the design of OLEDs, while the results here show that phosphorescence in dilute polymer films is also not suitable in this regard.…”
Section: Resultsmentioning
confidence: 72%
“…The most popular blue phosphor used in the field of PhOLEDs is the bis[2‐(4,6‐difluorophenyl)pyridinato‐C 2 ,N](picolinato)iridium(III) commonly abbreviated FIrpic. [ 31 ] However, FIrpic displays an E T of 2.67 eV (measured in 2‐methyl‐tetrahydofuran (2‐MeTHF) at room temperature (RT), [ 32 ] other values exist depending on the experimental conditions, see ref. [ 32 ] ) and is considered as a sky blue or greenish‐blue emitter (λ max = 465 and 497 nm in 2‐MeTHF).…”
Section: Part I Single‐layer Pholedsmentioning
confidence: 99%
“…[ 31 ] However, FIrpic displays an E T of 2.67 eV (measured in 2‐methyl‐tetrahydofuran (2‐MeTHF) at room temperature (RT), [ 32 ] other values exist depending on the experimental conditions, see ref. [ 32 ] ) and is considered as a sky blue or greenish‐blue emitter (λ max = 465 and 497 nm in 2‐MeTHF). Its HOMO/LUMO energy levels obtained from electrochemical studies in CH 2 Cl 2 + Bu 4 NPF 6 0.2 m are of ‐5.55/‐2.52 eV.…”
Section: Part I Single‐layer Pholedsmentioning
confidence: 99%
See 2 more Smart Citations